The Influence Of Customer Reviews And Customer Ratings On Purchasing Decisions For Beauty Products Garnier Micellar Water In Tiktok Shop - Fitriyani, Nunik Ina; Susanto, Heri; Rumna, Rumna (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of the study was to determine Customer Review and Customer Rating simultaneously on purchasing decisions for garnier micellar water beauty products at tik tok shop. This study uses a type of causal associative research with a quantitative approach. The population in this study were all consumers who had purchased Garnier Micellar Water products at Tik Tok Shop and the total sample used was 100 respondents with sampling techniques using Non Probability Sampling with a purposive sampling approach. Data collection was carried out by distributing questionnaires with data analysis used validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, determination test, t test and f test. Based on the T test results, it is found that each of the independent variables Customer Review and Customer Rating has an effect on purchasing decisions. In the Coefficient of Determination (R2) test, it can be seen that the Adjusted R Square value obtained is 0.538 (53.8%). This shows that the independent variables (Customer Review and Customer Rating) have a strong ability to explain the dependent variable (Purchase Decision) in this study. The remaining 46.2% will be influenced by other factors that cannot be explained in this study. Keywords: Customer Review, Customer Rating, Purchase Decision